Answer to ECG Quiz 34 - Millar, R. Scott (SA Heart Journal, 2017)
What appears to be sinus bradycardia or sinus arrest may be due to non-conducted atrial premature complexes. Premature P-waves may block because they fall within the normal AV nodal refractory period. Voltage criteria for LVH may still apply in the presence of LBBB.